ANALYSIS OF THE COORDINATES OF CHANGE RELATED TO INITIAL LABOUR AND TECHNICAL TRAINING (PEDAGOGICAL DIAGNOSTICS IN THIS EDUCATIONAL SEGMENT) - Klinkov, G.T; Naydenova, V.N (Хуманитарни Балкански изследвания, 2020)
The introduction into educational use of the subject Technology and Entrepreneurship at the end of 2016 put to the scientific and methodological community a number of tasks classified as strategic.The relatively clear methodological and meaningful model of conducting the learning process focuses on the existing methodology for planning and conducting pedagogical research related to the work and work preparation of students in different age groups. The traditions in this regard built over the years are mainly related to the formation of a basic methodology that reflects in 9-10 years the accumulated changes and the need to bring out a new educational, conceptual model related to work, technology and technology. In general, the research toolkit focuses on planning and conducting statistically available research methods that are able to measure mainly and mainly a basic variable characteristic of current educational practice. For these main reasons, a comprehensive study of the possibilities for diagnosis of technical and technological training in different school ages is required on the basis of a detailed interpretation of its individual, time-segregated countries. The article is part of a systematic and long-standing monograph study related to the pedagogical diagnostics of the primary specialized training of the students of the University of SS. It is necessary in this course of interpretation to link the possible diagnosis in 1-4th grade to that in kindergarten on the basis of the new model of training adopted in 2016 in the different age groups of this institution